Effects of MWCNTs on the Improved Mechanical Characteristics of Cementitious Composite - Gnanasaravanan, S.; Ayeshamariam, A.; Saravanakkumar, D.; Nagarani, N.; Baraneedharan, P.; Mohamed, S.B. (Current Physical Chemistry, 2025)
IntroductionConcrete's filler material gets strengthened over time by specific chemical reactions that harden it. Multi-walled carbon nanotubes (MWCNTs) are more frequently used as fillers than SWCNTs, owing to their lower cost of production and their superior reinforcement properties in cement composites.MethodsMechanical properties like compressive strength, splitting tensile strength, and modulus of elasticity are proportional to the water/cement ratio (w/c) and are considered critical criteria in the design of structural elements.ResultsThe aim of the present work was to prepare, characterize, and determine the effects that multi-walled carbon nanotubes (MWCNTs) can have on the mechanical strength of various matrix cementitious composites.ConclusionThe results showed that the addition of multi-walled carbon nanotubes to the concrete greatly improved both its compressive strength and its splitting tensile strength.
Keywords: anthropogenic carbon dioxide